Heterogeneity Spectrum of Earth's Upper Mantle Obtained from the Coherence of Teleseismic P Waves (Communications in Computational Physics, 2020)
Fluctuations in log-amplitude and travel time of teleseismic P wavesrecorded by the EarthScope USArray are used to invert for the heterogeneity spectrumof P-wave velocity in a 1000 km thick region of the upper mantle beneath the array.These fluctuations are used to form coherence functions. Best fits to joint transversecoherence functions require a depth dependent heterogeneity spectrum, with peaks innarrow depth ranges. These peaks agree well with peaks predicted for the temperature derivative of seismic velocity from models of the chemistry and phase of silicatemineral assemblages appropriate for the upper mantle, correlating with the depths ofphase changes. The results show that chemistry and phase act in concert with lateraland depth variations in temperature to produce the observed heterogeneity in seismicvelocities in the upper mantle at spatial scales from 50 to 300 km.
Keywords: Stochastic tomography; geophysical inversion.